An SOFC anode model using TPB-based kinetics. (16th October 2020) - Tabish, A.N.; Patel, H.C.; Chundru, P.; Stam, J.N.; Aravind, P.V.
Abstract: Fundamental studies focusing on the electrode kinetics are essential in understanding the fuel cell operation and optimizing the electrode designs. In this study, we determined the triple-phase boundary (TPB)-based kinetics of hydrogen electrochemical oxidation using nickel patterned electrode experimental data and the Butler-Volmer formalism of the oxidation process. The same kinetics are then incorporated in a cermet electrode electrochemical model to estimate the effective TPB density of the nickel/yittrium-stabilized zirconia cermet anode. The kinetics are found to be of the same order of magnitude as previously determined by the microstructure reconstruction of cermet anode. Simulation results further revealed that the effective TPB density is several orders of magnitude lower than the typically reported physical densities of the cermet anode that possibly suggests that only a minor fraction of the physical TPB is actually required or available to produce the cell current at given cell voltage. The effect of various operating conditions on the anode activation overpotential is also investigated and discussed in this study. Highlights: TPB-based kinetics were derived from pattern anode for use in cermet electrode model. Simulated effective TPB density of cermet was compared with reported physical density. Simulation revealed several orders of magnitude lower density than physical values. Only minor fraction of TPB density is expected to participate for current production.